Agronomic properties and nutritional profile of guinea-stylo mixture sown at different planting pattern - Mohamed Zain, Nurulain (2015)
Guinea-Stylo was established to study the effect of different planting pattern on forage production, agronomic properties and nutritive quality of Guinea-Stylo mixture. The varieties are Stylosanthes guianensis CIAT 184 and Megathyrsus maximus mixture were assessed at ladang 2, University Putra Malaysia from early April until October 2014 by using randomized complete block design (RCBD). The treatment was different types of planting pattern and was arranged in the 3m x 4m plotting system. Production, morphological aspect and nutritive value were assessed in this project. The Guinea-Stylo was sampled at 1st, 2nd, and 3rd harvested. This samples was analysed for crude protein (CP%), acid detergent fiber (ADF%), acid detergent lignin (ADL%), Neutral detergent fiber (NDF%), dry matter basis and ash percentage in the laboratory of Animal Science Department, Faculty of Agriculture (UPM). Botanical composition, number of plant per m2, leaves to stem ratio and plant height also were assessed. There are significant differences (P<0.05) in yield production in different planting pattern. The yield of Guinea grass and Stylo were increased at every cutting and this shows that the rate of growth of the plant was very high but it depends on type of different planting pattern. There are also significant differences (P<0.05) on ADF, NDF, ADL, CP and DM but not significant differences on (P>0.05) observed in ash. There are significant difference (P<0.05) on botanical composition, plant number per m2, plant height, and leaves to stem ratio observed.